Experiences with mucormycosis during COVID times in a government hospital in Kerala-a case series - Sreenath, Sarada; Ravi, Anil Kumar Arupathuparayil (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Mucormycosis is a rare invasive fungal infection which is often fatal. At the time of COVID-19 pandemic, there has been a sudden increase in the number of reported cases of mucormycosis. In this case series 10 cases of mucormycosis presented in our hospital during the COVID season are discussed. Of the 10 cases, only 8 patients had history of COVID infection. The predominant comorbidity was diabetes which was detected in all except one patient. But with timely diagnosis and appropriate management majority of the patients survived. Lesser symptoms and better prognosis were observed in patients without previous history of COVID.